1964
DOI: 10.1084/jem.120.2.267
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterial Pseudotuberculosis in Mice

Abstract: The susceptibility of mice to experimental infection with Corynebacterium kutscheri was studied by comparing the host response to this organism of mice obtained from 31 different colonies, representing 15 different genetic types. A standardized infective dose, administered intravenously, made it possible to separate the animals into two sharply differentiated groups. All the animals of the following colonies died: Swiss Lynch, Swiss R/J, A/Jax, Princeton, RFVL, and CF1 (SPF). All the animals of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

1966
1966
1997
1997

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 9 publications
0
19
1
Order By: Relevance
“…This question of the microbial states during latent and dormant infections has been discussed elsewhere (6,7) and is considered in detail in a more recent report by Pierce-Chase, Fauve, and Dubos (12). The fact that these acid-fast forms were readily demonstrable at the end of therapy in those 26 wk drug regimen experiments in which there has been no revival at all, casts some doubt on the possibility that they represent revivable tubercle bacilli.…”
Section: Discussionmentioning
confidence: 93%
“…This question of the microbial states during latent and dormant infections has been discussed elsewhere (6,7) and is considered in detail in a more recent report by Pierce-Chase, Fauve, and Dubos (12). The fact that these acid-fast forms were readily demonstrable at the end of therapy in those 26 wk drug regimen experiments in which there has been no revival at all, casts some doubt on the possibility that they represent revivable tubercle bacilli.…”
Section: Discussionmentioning
confidence: 93%
“…This study utilizes a common mouse pathogen, Corynebacterium kutscheri, which causes an often fatal pseudotuberculosis in mice. Pierce-Chase, Fauve, and Dubos have recently demonstrated large strain differences in susceptibility to disease caused by this organism (13). The same workers also showed that corynebacterial pseudotuberculosis could be activated by the hydrocorfisone treatment of mice harboring latent C. kutscheri (14).…”
mentioning
confidence: 75%
“…Saline-treated mice were sacrificed upon the death of corresponding hydrocortisone-treated mice. The kidneys, livers, lungs, hearts, and spleens of experimental and control mice were examined for the macroscopically visible yellow-white nodules characteristic of pseudotubercuiosis caused by infection with C. k~sched (13)(14)(15). Impression smears of the above named organs were stained and examined for corynebacterial-like microorganisms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations